DEVELOPING A PJOK MANAGEMENT SYSTEM IN KABUPATEN ACEH BESAR (A STUDY ON THE INTERVENTION OF THE PUBLIC POLICY TO ENHANCE THE PJOK SCHOOL MANAGEMENT QUALITY) - Syamsulrizal, Syamsulrizal; KS, Soegianto (The Journal of Educational Development, 2016)
This research aimed to develop a Physical Education, Sports, and Health (PJOK) learning in the form of public policy intervention through the determination of physical fitness as an element of school accreditation assessment at schools in Kabupaten Aceh Besar. This qualitative research made use of a natural approach. The subject of this study was the stakeholders at the district of Aceh Besar. The data were drawn using the purposive and snowball technique completed with the triangulation method focusing on emic perspective. Meanwhile, the data were analyzed qualitatively. The result of this study shows that the PJOK learning at schools in Kabupaten Aceh Besar had been running properly. Nevertheless, theories presentation dominated classes sessions compared to practices. Viewed from the quality and quantity, the PJOK teacher as the main human resources was considered fulfilling the standard. Nevertheless, after being reviewed within the existing bureaucratic structure there was no area which was responsible for the sports development at school. The financing for PJOK teaching-learning processes from the APBK budget had not been specifically allocated according to its needs. According to the standard, the number of facilities was still very limited. The research subject as a whole hoped that there was serious attention from the regional government to the PJOK teaching-learning processes by issuing specific policy concerning this matter. In conclusion, all subjects of this study stated their agreement if the government issues a public policy by determining physical fitness as one of the assessment elements of school accreditation at the education unit in Kabupaten Aceh Besar. In order to implement the policy, it is necessary for the district council (DPRK) of Kabupaten Aceh Besar to issue a legal foundation in the form of district regulation (Qanun).